dy/dx=-cos(xy)+xy sin(xy)/2y-x^2 sin(xy)
Given differential Equation is "\\frac{dy}{dx} = \\frac{-cos(xy)+xysin(xy)}{2y-x^2sin(xy)}"
It can be written as, "(cos(xy)-xysin(xy))dx +(2y-x^2sin(xy))dy = 0"
Comparing with "Mdx +Ndy = 0"
For exact differential equation,
"\\frac{\\partial N}{\\partial x} =\\frac{\\partial M}{\\partial y}"
Then
"\\frac{\\partial N}{\\partial x} = -2xsin(xy) -x^2ycos(xy)"
"\\frac{\\partial M}{\\partial y} = -2xsin(xy) -x^2ycos(xy)"
Hence equation is exact differential equation.
Integrating both sides,
"\\int (cos(xy)-xysin(xy))dx +\\int (2y-x^2sin(xy))dy = C"
"\\frac{sin(xy)}{y} - \\frac{sin(xy)}{y} + xcos(xy) + y^2 = C"
"xcos(xy) + y^2 = C"
Comments
Leave a comment